Upaya Penurunan Defect Porosity Pada PT. EPI Menggunakan Metode PDCA - Saryanto, Saryanto; Meri Prasetyawati, Meri Prasetyawati; MP, Renty Anugerah; Dewiyani, Leola; Sudarwati, Wiwik (Universitas Muhammadiyah Sorong, 2024)
Eratek Prima Indonesia is a company operating in the manufacturing industry, especially conveyor products. PT. Eratek Prima Indonesia produces the Conveyor Carousel type, which is a type of conveyor used to transport passenger luggage from the plane to the arrival hall at the airport. From the conveyor carrousel production data for August 2021 – January 2022, in the production department it was found that the most defects occurred in the welding process with the highest percentage of defects, namely porosity defects of 75%, which means it exceeds the allowance standard by less than 30%. Based on this data, it shows that a high percentage of defects can disrupt the production process and must be controlled. The method used to solve this problem is to use the PDCA method. PDCA is a useful tool for continuous improvement and FMEA is a tool frequently used in quality improvement methods. The results of this research are to reduce the volume of porosity defects. Improvement efforts made to reduce the volume of porosity defects are carrying out regular training to improve employee skills, cleaning the material to be welded, welders paying attention to the standard position of the welding wire, replacing welding handlebars that are worn out due to use. once every month. After the repairs were carried out, the results of the reduction in defect volume were now 29% in accordance with company standards.